Correlation of Cardiovascular Risk Factors and Severity of Coronary Artery Disease in Acute Myocardial Infarction - AMIR BUTT, AYESHA LIAQAT, LIAQAT ALI, AKMAL FAIZ, (Journal of Fatima Jinnah Medical University, 2018)
Background: Coronary artery disease is the major cause of death world over. There are different risk factors which are important for the development and progression of coronary artery disease. In this study I tried to established the correlation of cardiovascular risk factors in acute myocardial infarction and their relation with severity of coronary artery disease. Methods: This is a prospective study of 200 cases of acute myocardial infarction who were admitted in Wapda hospital Lahore from April 2013 to January 2015.All of them underwent coronary angiography. Patients were divided into two main groups, ST –elevation myocardial infarction (n=125) and Non ST- elevation myocardial infarction (n=75) and then patients with different cardiac risk factors such as diabetes mellitus, hypertension, hyperlipidemia, smoking and obesity were categorized and compared according to their presentation and then patients were regrouped according to the number of cardiovascular risk factors into two groups, one with two or less than two risk factors and other with more than two risk factors and in the end severity of coronary artery disease was compared among these two groups. Results: There is strong association between cardiac risk factors and angiographic findings in patients with acute myocardial infarction.. Among STEMI patients,67(33.5%) were diabetic, 51(25.5%) were hypertension,28(14%) were hyperlipidemia, 35(17.5%) were smokers, and 19(9.5%) were obese. Among patients with NSTEMI, 27(13.5%) were diabetic, 17(8.5%) were hypertensive,10(5%) had hyperlipidemia,14(7%) were smokers and 7(3.5%) were obese. In STEMI group, CAD on angiography was severe in 105(84% ) patients and moderate disease was present in 20(16%) patients, single. In NSTEMI group of 75 patients, 1(1.25%) patient has mild disease,11(13.75%) moderate disease and 68(85%) severe disease. Among STEMI patients, 38(19%) had two or less than two risk factors and 87(43.5%) were having more than two risk factors Among NSTEMI group, 26(13%) patients had two or less than two risk factors, 49 (24.5%) patients had more than two risk factors. In the group with risk factors two or less than two,15(7.5%) patients had single vessel disease,17(8.5%) double vessel disease,23(11.5%) had triple vessel disease,6(3%) left main disease and only 7(3.5%) patients had diffuse CAD on angiography. Among the group with risk factors more than two 87(43.5%) were suffering from STEMI and 49(24.5%) were suffering from Non-STEMI.28(14%) patients had single vessel disease,26(13%) double vessel disease,66(33%) triple vessel disease,9(4.5%) left main disease and only 15(7.5%) patients had generalized diffuse disease. Conclusion: There is very strong association between cardiac risk factors and severity of coronary artery disease in acute myocardial infarction. The greater are the numbers of risk factors, more severe and complex is the disease on angiography and lesser is the number of risks factors, simpler and less complex is the disease